2015
DOI: 10.1093/carcin/bgv037
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming and dysregulated metabolism: cause, consequence and/or enabler of environmental carcinogenesis?

Abstract: Environmental contributions to cancer development are widely accepted, but only a fraction of all pertinent exposures have probably been identified. Traditional toxicological approaches to the problem have largely focused on the effects of individual agents at singular endpoints. As such, they have incompletely addressed both the pro-carcinogenic contributions of environmentally relevant low-dose chemical mixtures and the fact that exposures can influence multiple cancer-associated endpoints over varying times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 275 publications
2
85
0
2
Order By: Relevance
“…This observation goes beyond answering a biological question, as metformin is a widely used drug in patients with type 2 diabetes (Singh, 2014). Indeed, its inhibition of trained immunity might have undesired consequences on antimicrobial host defense; on the other hand, it may represent a potential new drug to be employed in certain inflammatory diseases with excessive inflammation (Robey et al, 2015; Singhal et al, 2014; Tan et al, 2015). In contrast to glycolysis, the oxidative branch of PPP does not seem to have a major impact on trained immunity.…”
Section: Discussionmentioning
confidence: 99%
“…This observation goes beyond answering a biological question, as metformin is a widely used drug in patients with type 2 diabetes (Singh, 2014). Indeed, its inhibition of trained immunity might have undesired consequences on antimicrobial host defense; on the other hand, it may represent a potential new drug to be employed in certain inflammatory diseases with excessive inflammation (Robey et al, 2015; Singhal et al, 2014; Tan et al, 2015). In contrast to glycolysis, the oxidative branch of PPP does not seem to have a major impact on trained immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that changes in cellular metabolism can alter the expression of specific microRNAs and promote epigenetic changes in tumor cells (Arora et al, 2015; Bishop and Ferguson, 2015; Chan et al, 2015). Although some of these interactions are mentioned above, in-depth discussions of all of the interactions that occur between cancer and metabolism are beyond the scope of this review and the reader is referred to a number of reviews on these subjects (Gatenby and Gillies, 2004; Vander Heiden et al, 2009; Cantor and Sabatini, 2012; Ward and Thompson, 2012; Semenza, 2013; Gaude and Frezza, 2014; Masson and Ratcliffe, 2014; Boroughs and DeBerardinis, 2015; Casey et al, 2015; Robey et al, 2015; Asati et al, 2016; Barron et al, 2016; Bost et al, 2016; Molon et al, 2016; Pavlova and Thompson, 2016; PĂ©rez-Escuredo et al, 2016). The fact that metabolic dysregulation is seen in virtually all tumor cells has led to suggestions that a promising therapeutic strategy may be to exploit this feature.…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…these observations, mechanistic studies in animal and cell models have shown that metabolic dysfunction upon contaminants exposure occurs in various cell type and tissue, such as liver, muscle, adipose tissue and skin [15][16][17]. Pollutant induced-metabolic reprogramming is characterized by alterations in glucose metabolism (reduced gluconeogenesis and glycogenogenolysis), lipid metabolism (stimulated lipogenesis and qualitative changes in lipid species), and a strong impairment in energy metabolism due, at least in part, to a major mitochondrial dysfunction [18].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The hierarchical relationship between AhR, metabolic reprogramming, and EMT/migration upon AhR remain to decipher. AhR ligands should be challenged in order to determine if the AhR-induced metabolic shift is required to achieve EMT and migration, or whether it is the AhR-induced EMT that triggers metabolic changes [18].…”
Section: -3 Metastasis: Migration and Emt Triggered By Ahrmentioning
confidence: 99%